Student Satisfaction Analysis of Service Quality University of Sumatera Utara (USU) Library with Fuzzy Service Quality Method - Mirdayani Zega; James Peter Marbun (JMEA : Journal of Mathematics Education and Application, 2023)
Lack of service quality becomes one obstacle to student satisfaction. Service quality can be known by comparing the service that is in real acceptable with the service that the student expects. In this research method used to measure the level of satisfaction of acceptable service and which the student expects is the Fuzzy Service Quality method. The Fuzzy method is a method used to resolve issues where descriptions of activities, research and assessment are subjective, uncertain and inappropriate. The Fuzzy method is combined with the Service Quality method so that the student’s perception and expectation measurement can be measured easily and precisely. In Service Quality There are five dimensions that are used to improve the quality of service such as Tangible, Reliability, Responsiveness, Assurance and Empathy. The results of this study show that the gap value of the five dimensions has a negative value, meaning that the quality of service has not been expected so that the students perceived dissatisfaction occurs. This indicates that the quality of service provided by the library needs to make repairs, one of them on the physical attributes (Tangible) 6 with the availability question and ease of Internet access. At the value of gap per dimension, the dimensions that need to be prioritized by the library of USU to be done improvement is the dimension of Empathy.